Recurrent Keratocystic Odontogenic Tumor After Effective Decompression. Issue 5 (July 2016) - Zhang, Qian; Li, Wei; Han, Fangkai; Huang, Xiaofeng; Yang, Xudong
Abstract : Abstract: Keratocystic odontogenic tumor (KCOT) has potential aggressive and infiltrative behavior. Decompression has been widely preferred for large KCOTs due to safety and lower recurrence rates. However, KCOT is still likely to recur even after effective decompression. Here, we present a rare and interesting case of recurrent KCOT after effective decompression with adjunctive enucleation. Redecompression was then performed again, and the effect was still satisfactory on long-term follow-up.